Distal Adding-on and Risk Factors in Severe and Rigid Scoliosis. Issue 3 (February 2017) - Zang, Lei; Hai, Yong; Yuan, Shuo; Su, Qingjun; Yang, Jincai; Guan, Li; Kang, Nan; Meng, Xianglong; Liu, Yuzeng; Fan, Ning
Abstract : Study Design: A retrospective study. Objective: The aim of this study was to identify associated risk factors of distal adding-on in severe and rigid scoliosis. Summary of Background Data: Previous work has evaluated the challenges in the treatment of patients with severe and rigid scoliosis and the risks of complications. Furthermore, although several studies have investigated postoperative distal adding-on and attendant risk factors in Lenke type 1A scoliosis, very few have focused on distal adding-on in severe and rigid scoliosis. Methods: In this study, 48 consecutive patients with severe and rigid scoliosis underwent posterior spinal fusion surgery. The parameters of preoperative, immediately postoperative, and minimum 2-year follow-up radiographs were evaluated. The patients were classified as positive or negative for distal adding-on at follow-up, and risk factors were comparatively analyzed in the two groups. Results: The average Cobb angle and flexibility of the main thoracic curve (MTC) were 107.4° ± 15.9° and 16.4% ± 10.2%, respectively, before surgery. Distal adding-on was observed in 12 patients (25.0%) at follow-up. Univariate analysis identified several factors significantly associated with distal adding-on. Furthermore, significant independent risk factors identified by stepwise logistic regression analysis included the correction rate of the MTC immediately after surgery (odds ratio: 1.107, 95% confidence interval: 1.024–1.197, P  = 0.011) and the difference between the lower instrumented vertebra (LIV) and last touching vertebra (LTV) levels (odds ratio: 0.121, 95% confidence interval: 0.028–0.518, P  = 0.004). Conclusion: In severe and rigid scoliosis, a high correction rate of the MTC immediately after surgery and the LIV level above the LTV were significantly associated with distal adding-on. Level of Evidence: 3